Comparative Performance Analysis of Workload on Enterprise GPUs with Consumer Platforms Accelerated by CUDA Graphs - Retzlaff, Leandro L.; Pereira, Calebe C.; Veltri, Helena P.; Faganello, Murilo; Klein, William T.; Roque, Alexandre S. (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
This work investigates the feasibility of reproducing benchmarks originally run on datacenter GPUs such as the NVIDIA A100 and RTX 8000 using consumer-grade graphics cards, focusing on the NVIDIA GeForce RTX 3050 and GTX 1060 with CUDA Graphs support. Seven NAS Parallel Benchmarks (BT, LU, SP, EP, IS, MG, and CG) are evaluated across problem classes W, A, B, and C. Results show that the RTX 3050 delivers stable performance, typically 6×–12× slower than the A100, while VRAM limitations severely constrain the GTX 1060 for larger-scale problems. Although enterprise GPUs remain essential for massive, memory-bound workloads, modern consumer hardware combined with CUDA Graphs enables economical reproduction of moderate scientific experiments, supporting the democratization of high-performance computing research.